Regional trade agreements and agricultural trade: An analysis of Zimbabwe's agricultural trade flows - Admire Chawarika; Faustino Madzokere; Agrippa Murimbika (Cogent Economics & Finance, 2022)
The main aim of the study was to assess the impact of Economic Partnership Agreement (EPA) and Southern African Development Community Free Trade Area (SADC-FTA) on Zimbabwe's agricultural trade flows. Results highlight that Zimbabwe's membership in EPA initiated in 2012, enhanced the country's agricultural trade flows by 307.96%. Membership in SADC-FTA initiated in 2008 has enhanced the country's agricultural trade flows by 437.09%. Other independent variables including exchange rates and GDP negatively impacted the country's agricultural trade flows. From the empirical findings, it is critical for the government to conduct impact assessments.
Keywords: 330; agricultural trade flows; regional trade agreements; fixed effects; Zimbabwe; EPA